2020
DOI: 10.1002/slct.201902991
|View full text |Cite
|
Sign up to set email alerts
|

Electrodeposition of Three‐Dimensional Network Nanostructure PEDOT/PANI for Simultaneous Voltammetric Detection of Ascorbic Acid, Dopamine and Uric Acid

Abstract: In this study, poly(3,4-ethylenedioxythiophene) (PEDOT) and polyaniline (PANI) were electrodeposited via cyclic voltammetry (CV) on glass carbon electrode (GCE) layer by layer. The prepared electrode (GCE/PEDOT/PANI) was used for the simultaneous sensitive determination of ascorbic acid (AA), dopamine (DA) and uric acid (UA) at different oxidation potentials. The peak distances of AA and DA, DA and UA, AA and UA were 216 mV, 104 mV, 320 mV, respectively. For individual detection of AA, DA and UA, the linear ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“…The minimized distortion of GO5-zigzag-B reduced the stress of the graphene plane. This behavior was confirmed by the previous DFT work by Yan et al [ 15 ]. The second most stable configuration was GO5-para, where all the pairs of carbon atoms attached to all epoxy groups were aligned in parallel, and all ten occupied carbon atoms formed a cluster.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The minimized distortion of GO5-zigzag-B reduced the stress of the graphene plane. This behavior was confirmed by the previous DFT work by Yan et al [ 15 ]. The second most stable configuration was GO5-para, where all the pairs of carbon atoms attached to all epoxy groups were aligned in parallel, and all ten occupied carbon atoms formed a cluster.…”
Section: Resultssupporting
confidence: 89%
“…These made graphene an ideal material for developing biosensors. Many studies have reported electrode modification to improve the simultaneous determination of AA, DA, and UA in the CV and differential pulse voltammetry (DPV) experiments [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ], e.g., the use of multilayer graphene nanoflake films (MGNFs) [ 10 ], graphitic sheets or multi-walled carbon nanotube/metal composites [ 11 , 13 , 14 , 17 , 18 , 19 , 20 , 21 ], and conducting polymers [ 12 , 15 , 16 , 22 ]. Moreover, electrical [ 23 ] and chemical [ 24 ] reduced graphene oxides (rGO) were also employed for AA/DA/UA detections due to the better conductivity than GO and their cost-effectiveness.…”
Section: Introductionmentioning
confidence: 99%
“…The electrochemical sensor based on PPy/carbon-coated mesoporous silica (PPy/C#SiO 2 ) nanocomposite-modified glassy carbon electrodes (GCEs) demonstrated highly specific DA detection in the presence of the interference species [ 24 ]. In addition, PEDOT/PANi-modified GCEs was successfully prepared for simultaneous determination of DA, uric acid (UA) and ascorbic acid (AA) [ 25 ]. Among the common conducting polymers, PANi and its derivatives are the most popular conducting polymers in electroanalytical studies, which provide high sensitivity, selectivity, conductivity and good stability for detection of biomolecules [ 15 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, for the electrochemical determination of AA, electrodes with modified surfaces have been widely used, overlapping the fulling effect due to oxidation that may occur on the conventional electrode surfaces [ 6 ]. Carbon paste (CPE) [ 12 , 19 ] and glassy carbon (GCE) [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ] modified electrodes are the most commonly used for AA analysis in the available literature. Moreover, Pt modified electrodes with 3,4-diaminobenzoic acid and neutral red [ 34 ] or screen-printed electrodes (SPE) [ 35 , 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%